1999
DOI: 10.1210/jcem.84.7.5973
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate Transport Is Not Impaired in Pendred Syndrome Thyrocytes

Abstract: Pendred syndrome is the most common form of syndromic deafness, characterized by dyshormonogenic goiter associated with sensory-neural deafness. The gene responsible for the disease (PDS) has been cloned, but its function is as yet unknown and the connection between thyroid goiter and sensory-neural deafness remains an enigma. PDS codes for a novel protein, pendrin, which is closely related to a number of sufate transporters. Mechanisms by which abnormal sulfate transport could deleteriously affect iodide orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…Initial functional studies of pendrin in Xenopus oocytes and Sf9 insect cells, as well as functional studies using thyrocytes from patients with documented Pendred's syndrome, revealed that pendrin is unable to transport sulfate (21,22). In Xenopus oocytes, pendrin was shown to mediate uptake of chloride and iodide (21) and to act as a chloride/formate exchanger (23).…”
mentioning
confidence: 99%
“…Initial functional studies of pendrin in Xenopus oocytes and Sf9 insect cells, as well as functional studies using thyrocytes from patients with documented Pendred's syndrome, revealed that pendrin is unable to transport sulfate (21,22). In Xenopus oocytes, pendrin was shown to mediate uptake of chloride and iodide (21) and to act as a chloride/formate exchanger (23).…”
mentioning
confidence: 99%
“…Pendrin was first suggested to be a putative sulfate transporter on the basis of strong homologies with a number of known sulfate transporters, although sulfate transport is not impaired in PDS patients' thyroid cells (Kraiem et al 1999). Subsequently, the function of pendrin has been shown to be as a transporter of chloride and iodide (Scott et al 1999).…”
mentioning
confidence: 99%
“…Cette déduction n'expliquait pas les anomalies fonctionnelles de l'oreille interne et de la thyroïde dans le syndrome de Pendred. Il a d'ailleurs été rapidement démontré que si la pendrine est effectivement un transporteur ionique, elle ne transporte pas le sulfate mais elle échange le chlorure extracellulaire contre l'iodure, le formate ou le bicarbonate intracellulaires [3][4][5]. Les fonctions d'échan-geur Cl -/I -et Cl -/HCO 3 -rendent compte des rôles de la pendrine respectivement dans la thyroïde et dans l'oreille interne [6,7].…”
Section: Rôle Dans La Physiologie Rénale Et L'hypertension Artérielleunclassified
“…Cette réabsorption électrogénique de sodium génère un voltage transépithélial (négatif dans la lumière tubulaire par rapport à l'interstitium) qui permet la sécrétion de potassium par couplage de la [15]. Il existe aussi des cellules intercalaires non-A non-B qui expriment à la fois la pompe à proton et l'échangeur Cl -/HCO 3 -à la membrane apicale [14], et dont la fonction reste inconnue à ce jour.…”
Section: Les Multiples Fonctions Du Canal Collecteurunclassified
See 1 more Smart Citation